2016
DOI: 10.1016/j.rdc.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The Proteomics of Saliva in Sjögren's Syndrome

Abstract: Synopsis One of the main characteristics of primary Sjögren's syndrome (pSS) is chronic dysfunction and destruction of the salivary and lacrimal glands; hence, their secretory biofluids should reflect the glandular biological status. Saliva is a heterogeneous biofluid comprised of bio-molecules and omics constituents are altered in response to various diseases including pSS. In recent years, scientific effort has been undertaken for the purpose of evaluating saliva proteome to diagnose, monitor or prognosticat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 42 publications
0
45
0
3
Order By: Relevance
“…Many proteomic studies in the past were devoted to the characterisation of salivary biomarkers of Sjögren's syndrome (pSS) and this topic has been reviewed in depth 36 - 38 . A recent study investigated the expression of thymosins b4 and b10 in patients with pSS and in patients with autoimmune diseases: systemic sclerosis [SSc], systemic lupus erythematosus [SLE] and rheumatoid arthritis [RA], with and without sicca syndrome [ss].…”
Section: Human Saliva As Diagnostic Body Fluidmentioning
confidence: 99%
“…Many proteomic studies in the past were devoted to the characterisation of salivary biomarkers of Sjögren's syndrome (pSS) and this topic has been reviewed in depth 36 - 38 . A recent study investigated the expression of thymosins b4 and b10 in patients with pSS and in patients with autoimmune diseases: systemic sclerosis [SSc], systemic lupus erythematosus [SLE] and rheumatoid arthritis [RA], with and without sicca syndrome [ss].…”
Section: Human Saliva As Diagnostic Body Fluidmentioning
confidence: 99%
“…Saliva analysis has also been shown to diagnose more distal systemic malignancies such as breast cancer, lung cancer, ovarian cancer, and pancreatic cancer [40,41,42,43,44,45]. The main goal of these studies has been the discovery, verification, and validation of a panel of protein biomarkers so that they can be used in early detection of indicated diseases.…”
Section: Varieties Of Biomarkers For Diagnostics In Salivamentioning
confidence: 99%
“…Researchers who study the proteomics of Sjögren’s syndrome look closely at the production of cytokines (i.e., interferons and interleukins) and the downstream signaling pathway molecules as overexpressed or underexpressed constituents of saliva, in afflicted individuals versus a control population. Using mass spectrometry, Hu et al and other studies identified and further verified candidate proteins cathepsin D (CPD), α-enolase, and β2-microglobulin (B2M) as biomarkers that can discriminate primary SS from both systemic lupus erythematosus and healthy patients [43,44,45]. Additionally, statistical analysis showed that combining all three biomarkers yielded even higher sensitivity and specificity values compared to using them individually.…”
Section: Varieties Of Biomarkers For Diagnostics In Salivamentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first proteomics study on parotid saliva of patients with SS in 1999 by Beeley and Khoo, salivary proteomics has remained one of the most promising approaches to human disease biomarker identification with the advantage of being non‐invasively sampled. Several proteomics studies have shown differential protein expression in the saliva of patients with SS and healthy control subjects, and some studies have validated candidate markers . A few studies have performed proteomics analysis of saliva samples from patients with lymphoma …”
Section: Introductionmentioning
confidence: 99%